Mitigation of Gastrointestinal Disorders Through Community Health Education - Liu Han Li; Shilan Re (Akademi Sertifikasi Profesi Internasional, 2023)
Dyspepsia is a non-communicable condition that occurs globally, not solely in Indonesia. Dyspepsia is a syndrome characterised by pain or discomfort associated with heartburn, bloating, nausea, vomiting, belching, rapid satiety, and a sensation of fullness. This community service seeks to enhance awareness and perceptions among the regional community. The strategy is implemented to avoid dyspepsia via health counselling and the dissemination of informational pamphlets, which facilitate the adoption of healthy living practices through the maintenance of a proper diet and lifestyle. Students and a group of lecturers carried out this community service initiative. The outcome of community service is that the community comprehends dyspepsia and its prevention. The completion of this community service activity indicates a rise in community knowledge and attitudes. The majority of participants engaged in counselling activities by attentively considering the provided material and enquiring for further clarification when desired